Comorbidity of hypertension and chronic venous disease in men - V. M. Baev; T. F. Vagapov; S. A. Shmeleva (Российский кардиологический журнал, 2020)
Aim. To study the clinical manifestations and characteristics of lower extremity chronic venous disorders (CVD) in working-age men with hypertension (HTN).Material and methods. The study included 74 men with HTN at the age of 30-50 years and 41 men without HTN. HTN duration and regularity of antihypertensive medication intake were studied. We analyzed complaints and objective signs associated with CVD, their severity, structural and functional parameters of superficial, deep and perforator veins of the lower extremities using the triplex ultrasound. The prevalence and severity of cardiovascular risk factors among patients with HTN and CVD and patients with HTN and without CVD were analyzed.Results. Men aged 30-50 with HTN showed a high prevalence of complaints (68%) associated with CVD: evening heaviness and fullness in the legs; pain decrease at rest; a combination of pain, spasm and swelling in long-time standing. Objective signs of CVD were recorded in 83,8% of men with HTN (most often — telangiectasia (38%) and swelling (24%)). Men with HTN were diagnosed with more severe manifestations of CVD than men without HTN. In patients with HTN, episodic pain and evening perimalleolar swelling were 1,8 and 4 times more likely, respectively, than in men without HTN. The presence of CVD and HTN was not associated with cardiovascular risk factors. HTN in men was characterized by a large-diameter veins, pathological reflux, vein tortuosity, the presence of thrombotic masses and postthrombotic lesions. In patients with HTN, along with an increased blood flow velocity in the deep and perforator veins of the lower leg, a low velocity in the deep femoral veins was observed. This is the evidence of venous insufficiency even at rest. Orthostasis in men with HTN increased the frequency of reflux in superficial veins by 2-4 times, which proves latent venous insufficiency.Conclusion. HTN is characterized by an increase in the frequency and severity of symptoms and signs of CVD, which indicates their comorbidity.